A construção do campo da enfermagem obstétrica em Minas Gerais: um estudo genealógico - Rafaela Siqueira Costa Schreck (2023)
This is an interpretative qualitative study based on historical research, outlined from the following guiding question: “How did the construction of the field of obstetric nursing occur in Minas Gerais?”. It aims to analyze the construction of the field of obstetric nursing, in Minas Gerais, from the subjects involved in this process. The study is anchored in the philosophical conceptions of Michael Foucault, specifically, Genealogy, seeking to build a genealogical history that addresses the ruptures and continuities of events, centered on the microphysics of relationships, on the disputes, resistances and objectification of bodies, problematizing the practices of power, which produced a way of being, thinking, acting and feeling in obstetric nursing. The temporal outline covers the period from 1957, the year in which the first specialization in obstetric nursing was offered, in Minas Gerais, until 2011, with the institution of the Cegonha Network Program. The methodology adopts three paths: a review study, with the scoping review method for a better understanding of what has already been produced about midwifery in Brazil, and to map the characteristics of the scientific knowledge produced by and about the category; documentary research and thematic oral history. The documents taken as sources are part of the collection of the memory centers of the School of Nursing and the Faculty of Medicine of the Federal University of Minas Gerais. For oral sources, subjects involved directly or indirectly with the object were included. The documents and interviews used as a research source were submitted to Discourse Analysis explained by Michael Foucault. Research findings are discussed in three chapters. The first two chapters deal with the genealogical courses and events of obstetric nursing in Minas Gerais from 1957 to 1999 and from 1999 to 2011. The third chapter of the thesis addresses provenance as a genealogical construction, with the analysis of the repercussions of historical events for the way, feel and think of midwives. With this way of organizing the research, it is intended to bring, in addition to the presentation and discussion of the collected data, the steps that were followed and the processes of interpretation and analysis, in light of the Foucauldian framework. The collected data show the possibility of confirming the thesis postulated for the study. The force vectors and events that influenced the construction of the field of obstetric nursing in Minas Gerais indicate the formation of a knowledge specific to obstetric nurses, based on good practices in labor and birth care. This knowledge, characteristic of the professional category, inserted the specialist nurses in the obstetric scenario, capable of disputing spaces of practice and offering resistance to the model of medicalization of the female body. The process of this emergence is characterized by force vectors, struggle strategies, clashes and confrontations. The genealogical approach acts as a critical tool capable of highlighting the singularities of the research object's history, giving relevance to the data found and proposed analyses.